Relevansi Pemikiran Tajdid KH Ahmad Dahlan dengan Moderasi Beragama Berbasis Tasamuh Aktif - Aisya Gadhing Cemara; Siti Muazifah; Ni'matul Halizah (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
This research is motivated by the increasing phenomenon of intolerance, identity polarization, and narrowing of the meaning of religion in Indonesia which demands the strengthening of religious moderation based on contextual Islamic values. KH Ahmad Dahlan, as a figure of Indonesian Islamic reformer, offered a tajd?d (renewal) paradigm that combined rationality, spirituality, and social praxis. The purpose of this research is to analyze in depth the thought of tajd?d KH Ahmad Dahlan and its relevance in affirming religious moderation based on active tasamuh in contemporary Indonesia. This research uses a qualitative method with the type of library research, through content analysis of works, biography, and academic literature about KH Ahmad Dahlan. The results of the study show that Dahlan's thought emphasizes the importance of purifying the faith from superstition, heresy, and superstition; the integration of religious and general knowledge in education; and social charity as a tangible form of worship and religious moderation. The value of active tasamuh carried by Dahlan emphasizes participatory tolerance, not just permissiveness, namely respecting differences through social cooperation and inclusive public services. This thinking is relevant in four major domains: religious moderation, character education, socio-economic empowerment, and just public policy. Thus, the values of tajd?d Dahlan proved to be able to become the foundation of progressive Islam that encourages a plural society towards a peaceful, civilized, and beneficial life.